Effect of optimized food-based recommendations on nutrient intakes, hemoglobin levels, and memory performance of adolescent girls in East Java, Indonesia - Dini Suciyanti; Risatianti Kolopaking; Annasari Mustafa; Sugeng Iwan; Fiastuti Witjaksono; Umi Fahmida (Nutrition Journal)
Abstract Background FAO/WHO introduced food-based dietary guidelines (FBDG) to promote healthy dietary habits. To translate the FBDG, optimized food-based recommendations (FBR) can be developed using linear programming (LP) to address problem nutrients. Despite the importance of local-specific FBR for anemia prevention, no study has reported the effect of nutrition education which promoted FBR in adolescent girls. Therefore, this study aimed to investigate the effect of optimized FBR in adolescent girls in improving dietary and nutrient intakes, hemoglobin levels, and memory performance. Methods The intervention study was carried out in Malang District, Indonesia amongst 14–18 year adolescent girls. The study’s Indonesian slogan was Remaja which meant Active, Healthy, Smart, and Creative adolescents. The optimized FBR was developed using LP and translated into six key messages. Twenty-week nutrition education was integrated into the weekly school’s system. Results After 20 weeks, a significant increase in dietary practices (animal protein, liver, plant protein, vegetables), nutrient intakes (protein, fat, iron), and memory performance (digit span forward and backward) were found in the intervention group. In contrast, there was decreases in the control group’s intakes of animal and plant protein. Conclusions This finding shows that nutrition education with optimized FBR increased intakes of nutrient-dense food, protein, fat, iron, and memory performance (concentration). Nutrition education with optimized FBR should be integrated into the school system together with weekly iron supplementation for anemia prevention among these adolescent girls. Trial registration The study was registered on ClinicalTrials.gov (ID No: NCT03946475).